Analisis Wacana Kritis terhadap Representasi Gender dalam Iklan Elektronik di Era Globalisasi - Rizki, Putri Meylina; Agustin, Nur Shafira; Rahmawati, Zulfatri; Sununianti, Vieronica Varbi; Kurniawan, Deni Aries (Pusat Studi Wanita dan Keluarga UGM, 2024)
Globalization has brought significant changes in various aspects of human life, including the representation of gender in advertisements. This study aims to critically analyze the representation of gender change in electronic advertisements using a qualitative method, analyzed through Norman Fairclough's critical discourse analysis approach. The advertisements chosen for analysis are “Segampang Itu Nyuci Noda Kalau Ada Proclin” and the Sunlight product advertisement featuring a man, “Wih kok bisa Sunlight sebagus ini!”. The analysis is carried out using the three dimensions of discourse analysis identified by Fairclough: text, discourse practice, and social practice. The analysis results show that the representation of gender change in these electronic advertisements indicates that both ads function not only as tools for product promotion but also as instruments for social change. These advertisements support the discourse of gender equality and have the potential to influence public perceptions of gender roles within the household. Thus, advertisements do not merely reflect social reality but can also shape and alter societal views regarding the division of gender roles.